Analysis of Parents' Motivational Factors in Choosing Islamic Boarding Schools as a Means of Moral Development Based on Spiritual Values - Lathifa Umaiya; Nurul Yakin (Penerbit Hellow Pustaka, 2025)
This study is motivated by parents' concerns that raising children in this modern era has become an increasingly complex challenge. The rise in crime, misuse of technology, promiscuity, juvenile delinquency, and lack of supervision due to parents' busy schedules pose a serious threat to children's moral and psychological development. This situation requires parents to be more discerning in choosing the right educational environment for their children. One alternative chosen by many parents in facing these challenges is to enroll their children in Islamic boarding schools. This study aims to determine the motivation of parents in choosing Islamic boarding schools as a means of moral guidance for their children, the advantages that parents have experienced while sending their children to Islamic boarding schools, and the supporting and inhibiting factors for parents in sending their children to Islamic boarding schools. This study uses a descriptive sociological research method with a qualitative approach. The data sources for this study are parents/guardians of students. Meanwhile, data collection in this study was taken from several methods, namely observation, interviews, and documentation. The results of the study on parents' motivations in choosing Islamic boarding schools as a means of moral guidance include several factors: intensive moral guidance and supervision of children's behavior, the hope that children will become independent, disciplined, and have good character, and family background.